2021
DOI: 10.3390/agronomy11102056
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Photosynthetic Pigments Content in Non-Transformed and AtCKX Transgenic Centaury (Centaurium erythraea Rafn) Shoots Grown under Salt Stress In Vitro

Abstract: The effects of graded sodium chloride (NaCl) concentrations (0-, 50-, 100-, 150-, and 200-mM) on photosynthetic pigment contents in in vitro grown shoots of important medicinal plant species (Centaurium erythraea Rafn) were investigated. Non-transformed, one AtCKX1 and two AtCKX2 transgenic centaury lines, with altered cytokinin profiles, were used in this study. The chlorophyll (Chl) and carotenoid contents differed in the non-transformed and transgenic lines. In general, salinity significantly reduced the Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 78 publications
(90 reference statements)
2
10
0
Order By: Relevance
“…This work demonstrated that total Chl content was significantly decreased in control shoots grown on NaCl in comparison to the other control group of shoots grown on ½MS medium ( Figure 3 a). These results are in accordance with the results previously obtained in centaury shoots grown during NaCl-caused salt stress in vitro [ 37 , 39 ]. The lowest SNP concentration applied at pretreatment (50 μM) shown a positive effect on total Chl content in centaury leaves during salt stress.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This work demonstrated that total Chl content was significantly decreased in control shoots grown on NaCl in comparison to the other control group of shoots grown on ½MS medium ( Figure 3 a). These results are in accordance with the results previously obtained in centaury shoots grown during NaCl-caused salt stress in vitro [ 37 , 39 ]. The lowest SNP concentration applied at pretreatment (50 μM) shown a positive effect on total Chl content in centaury leaves during salt stress.…”
Section: Discussionsupporting
confidence: 93%
“…The results presented in this work showed that NaCl had negative effect on total carotenoid content in centaury shoots grown in control conditions ( Figure 3 b). Decreased carotenoid content was also recently reported in centaury shoots under salt stress in vitro [ 39 ]. In centaury shoots treated with NaCl, the application of SNP pretreatments resulted in increased total carotenoid content in comparison to control group of shoots grown on medium also supplemented with NaCl.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…According to Figure 5A, the increase in the ECw decreased the chlorophyll a content of yellow passion fruit by 17.38% per unit increase in electrical conductivity of water, i.e., in yellow passion fruit plants irrigated with ECw of 2.8 dS m -1 the chlorophyll a concentration was reduced by 41.54% compared to plants under the lowest value of ECw (0.7 dS m -1 ). The degradation of photosynthetic pigments in plants grown under water salinity is probably a consequence of increased toxic ions, increased activity of the chlorophyllase enzyme, and damage to the photosynthetic apparatus (Trifunovic-Momcilov et al, 2021). As noted by Lima et al (2020), the increase in ECw from 0.3 to 3.5 dS m -1 led to reduction in the Chl a concentrations of yellow passion fruit plants.…”
Section: Resultsmentioning
confidence: 88%